2020
DOI: 10.1101/2020.02.26.20028175
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ADHD is more closely linked to neurodevelopmental than externalizing and internalizing disorders: A genetically informed multivariate Swedish population study

Abstract: Background: While ADHD is currently classified as a neurodevelopmental disorder in the latest diagnostic manuals, the disorder shows phenotypic and genetic associations of similar magnitudes across neurodevelopmental, externalizing and internalizing disorders. This study aimed to investigate if ADHD is etiologically more closely related to neurodevelopmental than externalizing or internalizing disorder clusters after accounting for a general psychopathology factor. Methods: Full- and maternal half-sibling pair… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Further, emerging evidence from multivariate twin and family studies suggests that ADHD loads strongly onto a general genetic psychopathology factor. After accounting for this general factor, ADHD remains genetically associated with a specific neurodevelopmental factor, while genetic links to externalizing and internalizing psychopathology are considerably attenuated, supporting the neurodevelopmental etiology of ADHD (Du Rietz et al, 2020;Lahey et al, 2011;Pettersson et al, 2013Pettersson et al, , 2015. Although twin and family studies addressing non-psychiatric comorbidity in ADHD are sparse, genetic correlations with somatic/neurological conditions such as asthma, epilepsy and obesity (twin rg=0.20-0.30) are weaker than between ADHD and other psychiatric disorders Chen et al, 2019;Holmberg et al, 2015;Mogensen et al, 2011).…”
Section: Quantitative Genetic Studies Of Adhdmentioning
confidence: 97%
“…Further, emerging evidence from multivariate twin and family studies suggests that ADHD loads strongly onto a general genetic psychopathology factor. After accounting for this general factor, ADHD remains genetically associated with a specific neurodevelopmental factor, while genetic links to externalizing and internalizing psychopathology are considerably attenuated, supporting the neurodevelopmental etiology of ADHD (Du Rietz et al, 2020;Lahey et al, 2011;Pettersson et al, 2013Pettersson et al, , 2015. Although twin and family studies addressing non-psychiatric comorbidity in ADHD are sparse, genetic correlations with somatic/neurological conditions such as asthma, epilepsy and obesity (twin rg=0.20-0.30) are weaker than between ADHD and other psychiatric disorders Chen et al, 2019;Holmberg et al, 2015;Mogensen et al, 2011).…”
Section: Quantitative Genetic Studies Of Adhdmentioning
confidence: 97%
“…Studies have shown that nearly 70% of people with intellectual disability and ADHD also meet diagnostic criteria for autism spectrum disorder (ASD) (Perera 2021). Recent evidence points in the direction of genetic links between ADHD and the wider group of neurodevelopmental disorders (Rietz 2020). ASD and ADHD share aetiological factors and create greater morbidity and clinical challenges when they co-occur (Leitner 2014).…”
Section: Comorbid Psychiatric Disordersmentioning
confidence: 99%